Low-expansion ceramic product prepared from microcrystalline glass leftover materials and preparation method of low-expansion ceramic product
By combining microcrystalline glass scraps with other ceramic materials, low-expanded ceramic products are prepared, which solves the problem of resource waste and achieves efficient utilization of resources and improves product performance.
Patent Information
- Application Number
- CN202411672760.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-07
AI Technical Summary
The prior art cannot effectively utilize crystal-crystalline glass scraps, resulting in waste of resources and high cost processing problems.
Low-expanded ceramic products are prepared by combining microcrystalline glass scraps with watery kaolin, talc, firing Datong soil, tantalum oxide and niobium oxide, and processed by ball milling, screening, iron removal, filter pressing and dehydration, mud training, molding, glazing, firing and firing.
It realizes efficient utilization of resources, reduces the firing temperature of low-expanding ceramics, saves energy and reduces emissions, reduces costs, and improves the water absorption, expansion coefficient and thermal shock resistance of the product.
Smart Images

Figure CN119569420A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic materials, and in particular to a low-expansion ceramic product prepared from leftover microcrystalline glass and a preparation method thereof. Background Art
[0002] Glass-ceramics is a polycrystalline material with a fine microstructure that has been crystallized under controlled conditions. It has excellent physical and chemical properties such as mechanical strength, surface hardness, chemical stability, thermal expansion coefficient, and is widely used in the fields of construction machinery engineering, medicine, electronic technology, aerospace technology, etc. In the social development outline formulated by the State Science and Technology Commission, glass-ceramics is planned as a strategic development focus of the national comprehensive utilization action and a focus of environmental protection governance, and is called a new material across the century.
[0003] Lithium aluminum silicon system glass-ceramics has good strength, hardness, low thermal expansion coefficient, low dielectric parameters and other characteristics. It is a common binder material for diamond grinding wheels, and can also be used as LTCC packaging materials. It can also be widely used to manufacture telescope reflectors, laser gyroscopes, high-temperature cookers, tableware, barbecue oven panels, high-temperature observation windows, etc. In the manufacturing process, a lot of scraps and solid wastes such as waste will be generated due to processing. It is inevitable that impurities such as abrasives and abrasives are mixed in the waste, which cannot be recycled for reproduction, resulting in great waste. The current treatment method is to landfill or make low-quality building material fillers, which does not make full use of it. Summary of the invention
[0004] The purpose of the present invention is to overcome the deficiencies of the prior art and to provide a low expansion ceramic product prepared from microcrystalline glass scraps and a preparation method thereof which has simple process, low cost and is easy to use.
[0005] The present invention is achieved through the following technical scheme: a low expansion ceramic product prepared with microcrystalline glass scraps, characterized in that the weight percentage of the raw material formula of the low expansion ceramic product blank is: microcrystalline glass scraps 40-50wt%, halloysite 35-42wt%, talc 8-12wt%, burned datong clay 5-10wt%, tantalum oxide 1-5wt%, and niobium oxide 1-5wt%.
[0006] The chemical composition of the microcrystalline glass scraps is: SiO2 52.9-59wt%, Al2O3 25.2-31.1wt%, CaO 0.4-0.6wt%, MgO 2.6-3.9wt%, K2O 0.2-0.8wt%, Na2O 1.4-1.9 wt%, B2O3 5.5-8.8wt%, Li2O 4.22-5.68 wt%, and the ignition loss is 1.2-3.2 wt%.
[0007] The microcrystalline glass scraps are waste materials after microcrystalline glass is edged, punched and cut.
[0008] The method for preparing the low expansion ceramic product is characterized in that: the raw materials for the green body of the low expansion ceramic product are weighed according to a formula, and then the low expansion ceramic product is obtained through ball milling, screening, iron removal, filter pressing and dehydration, mud kneading, molding, glazing and firing.
[0009] The screening process is to pass through a 325-mesh sieve with a sieve residue of 0.05%.
[0010] The forming process adopts a rolling forming or a grouting forming method.
[0011] The glazing process is to first glaze by dipping glaze method and then glaze by spraying glaze method.
[0012] The sintering process has a maximum sintering temperature of 1220-1240° C., maintaining the maximum temperature for 45-60 minutes, rapidly cooling to 1150° C., maintaining the temperature for another 30-60 minutes, and then naturally cooling, and the sintering cycle is 10-12 hours.
[0013] The water absorption rate of the low expansion ceramic product is ≤0.5%, and the expansion coefficient is ≤2.5x10 -6 / ℃, thermal shock resistance is 350℃~20℃, one-time water cooling will not crack.
[0014] The present invention has the following beneficial effects: (1) The present invention uses a large amount of microcrystalline glass scraps, turning waste into treasure and making high-value use of it, and reduces the firing temperature of low-expansion ceramics, thereby saving energy, reducing emissions and lowering costs.
[0015] (2) In the present invention, the scraps of microcrystalline glass and the crystallizing agent tantalum oxide are introduced, and a solid solution of low-expansion cordierite, spodumene and quartz (Li2O·Al2O3·7.5SiO2) is precipitated during the firing process, as shown in the attached XRD spectrum. The solid solution has low water absorption and expansion coefficient, good thermal shock resistance, water absorption ≤0.5%, and expansion coefficient can reach ≤2.5x10 -6 / ℃, and its thermal shock resistance reaches 350℃~20℃ without cracking after one water cooling. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 Example 3: SEM scanning graph of the green body structure of the low expansion ceramic product obtained; Figure 2 Example 3: SEM scanning graph of the green body structure of the low expansion ceramic product obtained; Figure 3 Example 3: XRD scanning spectrum of the green body structure of the low expansion ceramic product obtained. DETAILED DESCRIPTION
[0017] In order to further explain the present invention and the technical means and effects adopted to achieve the predetermined invention purpose, the present invention is described in detail below in conjunction with preferred embodiments: Example 1
[0018] A low-expansion ceramic product prepared from microcrystalline glass scraps, wherein the weight percentage composition of the raw material formula of the low-expansion ceramic product blank is: 40wt% of microcrystalline glass scraps, 35wt% of halloysite, 12wt% of talc, 10wt% of burned datong clay, 2wt% of tantalum oxide, and 1wt% of niobium oxide.
[0019] The chemical composition of the microcrystalline glass scraps is: SiO2 52.9-59wt%, Al2O3 25.2-31.1wt%, CaO 0.4-0.6wt%, MgO 2.6-3.9wt%, K2O 0.2-0.8wt%, Na2O 1.4-1.9 wt%, B2O3 5.5-8.8wt%, Li2O 4.22-5.68 wt%, and the ignition loss is 1.2-3.2 wt%.
[0020] The microcrystalline glass scraps are waste materials after microcrystalline glass is edged, punched and cut.
[0021] The method for preparing the low expansion ceramic product is characterized in that: the raw materials for the green body of the low expansion ceramic product are weighed according to a formula, and then the low expansion ceramic product is obtained through ball milling, screening, iron removal, filter pressing and dehydration, mud kneading, molding, glazing and firing.
[0022] The screening process is to pass through a 325-mesh sieve with a sieve residue of 0.05%.
[0023] The forming process adopts a rolling forming method.
[0024] The glazing process is to first glaze by dipping glaze method and then glaze by spraying glaze method.
[0025] The firing process has a maximum firing temperature of 1240° C., which is maintained at the maximum temperature for 45 minutes and then rapidly cooled to 1150° C., maintained at the maximum temperature for another 30 minutes and then naturally cooled, and the firing cycle is 10 hours.
[0026] The water absorption rate of the low expansion ceramic product is 0.42% and the expansion coefficient is 2.22 x 10 -6 / ℃, thermal shock resistance is 350℃~20℃, one-time water cooling will not crack. Example 2
[0027] A low-expansion ceramic product prepared from microcrystalline glass scraps, wherein the weight percentage of the raw material formula of the low-expansion ceramic product blank is as follows: 45wt% of microcrystalline glass scraps, 40wt% of halloysite, 8wt% of talc, 5wt% of burned datong clay, 1wt% of tantalum oxide, and 1wt% of niobium oxide.
[0028] The chemical composition of the microcrystalline glass scraps is: SiO2 52.9-59wt%, Al2O3 25.2-31.1wt%, CaO 0.4-0.6wt%, MgO 2.6-3.9wt%, K2O 0.2-0.8wt%, Na2O 1.4-1.9 wt%, B2O3 5.5-8.8wt%, Li2O 4.22-5.68 wt%, and the ignition loss is 1.2-3.2 wt%.
[0029] The microcrystalline glass scraps are waste materials after microcrystalline glass is edged, punched and cut.
[0030] The method for preparing the low expansion ceramic product is characterized in that: the raw materials for the green body of the low expansion ceramic product are weighed according to a formula, and then the low expansion ceramic product is obtained through ball milling, screening, iron removal, filter pressing and dehydration, mud kneading, molding, glazing and firing.
[0031] The screening process is to pass through a 325-mesh sieve with a sieve residue of 0.05%.
[0032] The forming process adopts a rolling forming method.
[0033] The glazing process is to first glaze by dipping glaze method and then glaze by spraying glaze method.
[0034] The firing process has a maximum firing temperature of 1230° C., which is maintained at the maximum temperature for 50 minutes and then rapidly cooled to 1150° C., maintained at the maximum temperature for another 45 minutes and then naturally cooled, and the firing cycle is 11 hours.
[0035] The water absorption rate of the low expansion ceramic product is 0.46% and the expansion coefficient is 2.2 x 10 -6 / ℃, thermal shock resistance is 350℃~20℃, one-time water cooling will not crack. Example 3
[0036] A low-expansion ceramic product prepared from microcrystalline glass scraps, wherein the weight percentage composition of the raw material formula of the low-expansion ceramic product blank is: 50wt% of microcrystalline glass scraps, 35wt% of halloysite, 8wt% of talc, 5wt% of burned datong clay, 1wt% of tantalum oxide, and 1wt% of niobium oxide.
[0037] The chemical composition of the microcrystalline glass scraps is: SiO2 52.9-59wt%, Al2O3 25.2-31.1wt%, CaO 0.4-0.6wt%, MgO 2.6-3.9wt%, K2O 0.2-0.8wt%, Na2O 1.4-1.9 wt%, B2O3 5.5-8.8wt%, Li2O 4.22-5.68 wt%, and the ignition loss is 1.2-3.2 wt%.
[0038] The microcrystalline glass scraps are waste materials after microcrystalline glass is edged, punched and cut.
[0039] The method for preparing the low expansion ceramic product is characterized in that: the raw materials for the green body of the low expansion ceramic product are weighed according to a formula, and then the low expansion ceramic product is obtained through ball milling, screening, iron removal, filter pressing and dehydration, mud kneading, molding, glazing and firing.
[0040] The screening process is to pass through a 325-mesh sieve with a sieve residue of 0.05%.
[0041] The molding process adopts a grouting molding method.
[0042] The glazing process is to first glaze by dipping glaze method and then glaze by spraying glaze method.
[0043] The firing process has a maximum firing temperature of 1220° C., which is maintained at the maximum temperature for 60 minutes and then rapidly cooled to 1150° C., maintained at the maximum temperature for another 60 minutes and then naturally cooled, and the firing cycle is 12 hours.
[0044] The water absorption rate of the low expansion ceramic product is 0.36% and the expansion coefficient is 2.5 x 10 -6 / ℃, thermal shock resistance is 350℃~20℃, one-time water cooling will not crack. Example 4
[0045] A low-expansion ceramic product prepared from microcrystalline glass scraps, wherein the weight percentage composition of the raw material formula of the low-expansion ceramic product blank is: 40wt% of microcrystalline glass scraps, 38wt% of halloysite, 10wt% of talc, 6wt% of burned datong clay, 3wt% of tantalum oxide, and 3wt% of niobium oxide.
[0046] The chemical composition of the microcrystalline glass scraps is: SiO2 52.9-59wt%, Al2O3 25.2-31.1wt%, CaO 0.4-0.6wt%, MgO 2.6-3.9wt%, K2O 0.2-0.8wt%, Na2O 1.4-1.9 wt%, B2O3 5.5-8.8wt%, Li2O 4.22-5.68 wt%, and the ignition loss is 1.2-3.2 wt%.
[0047] The microcrystalline glass scraps are waste materials after microcrystalline glass is edged, punched and cut.
[0048] The method for preparing the low expansion ceramic product is characterized in that: the raw materials for the green body of the low expansion ceramic product are weighed according to a formula, and then the low expansion ceramic product is obtained through ball milling, screening, iron removal, filter pressing and dehydration, mud kneading, molding, glazing and firing.
[0049] The screening process is to pass through a 325-mesh sieve with a sieve residue of 0.05%.
[0050] The molding process adopts a grouting molding method.
[0051] The glazing process is to first glaze by dipping glaze method and then glaze by spraying glaze method.
[0052] The firing process has a maximum firing temperature of 1235° C., which is maintained at the maximum temperature for 45 minutes and then rapidly cooled to 1150° C., maintained at the maximum temperature for another 50 minutes and then naturally cooled, and the firing cycle is 11.5 hours.
[0053] The water absorption rate of the low expansion ceramic product is 0.44% and the expansion coefficient is 2.35x10 -6 / ℃, thermal shock resistance is 350℃~20℃, one-time water cooling will not crack. Example 5
[0054] A low-expansion ceramic product prepared from microcrystalline glass scraps, wherein the weight percentage composition of the raw material formula of the low-expansion ceramic product blank is: 42wt% of microcrystalline glass scraps, 35wt% of halloysite, 8wt% of talc, 8wt% of burned datong clay, 2wt% of tantalum oxide, and 5wt% of niobium oxide.
[0055] The chemical composition of the microcrystalline glass scraps is: SiO2 52.9-59wt%, Al2O3 25.2-31.1wt%, CaO 0.4-0.6wt%, MgO 2.6-3.9wt%, K2O 0.2-0.8wt%, Na2O 1.4-1.9 wt%, B2O3 5.5-8.8wt%, Li2O 4.22-5.68 wt%, and the ignition loss is 1.2-3.2 wt%.
[0056] The microcrystalline glass scraps are waste materials after microcrystalline glass is edged, punched and cut.
[0057] The method for preparing the low expansion ceramic product is characterized in that: the raw materials for the green body of the low expansion ceramic product are weighed according to a formula, and then the low expansion ceramic product is obtained through ball milling, screening, iron removal, filter pressing and dehydration, mud kneading, molding, glazing and firing.
[0058] The screening process is to pass through a 325-mesh sieve with a sieve residue of 0.05%.
[0059] The forming process adopts a rolling forming method.
[0060] The glazing process is to first glaze by dipping glaze method and then glaze by spraying glaze method.
[0061] The firing process has a maximum firing temperature of 1225° C., which is maintained at the maximum temperature for 55 minutes and then rapidly cooled to 1150° C., maintained at the maximum temperature for another 55 minutes and then naturally cooled, and the firing cycle is 12 hours.
[0062] The water absorption rate of the low expansion ceramic product is 0.48% and the expansion coefficient is 2.46 x 10 -6 / ℃, thermal shock resistance is 350℃~20℃, one-time water cooling will not crack. Example 6
[0063] A low-expansion ceramic product prepared from microcrystalline glass scraps, wherein the weight percentage composition of the raw material formula of the low-expansion ceramic product blank is: 40wt% of microcrystalline glass scraps, 36wt% of halloysite, 8wt% of talc, 10wt% of burned datong clay, 5wt% of tantalum oxide, and 1wt% of niobium oxide.
[0064] The chemical composition of the microcrystalline glass scraps is: SiO2 52.9-59wt%, Al2O3 25.2-31.1wt%, CaO 0.4-0.6wt%, MgO 2.6-3.9wt%, K2O 0.2-0.8wt%, Na2O 1.4-1.9 wt%, B2O3 5.5-8.8wt%, Li2O 4.22-5.68 wt%, and the ignition loss is 1.2-3.2 wt%.
[0065] The microcrystalline glass scraps are waste materials after microcrystalline glass is edged, punched and cut.
[0066] The method for preparing the low expansion ceramic product is characterized in that: the raw materials for the green body of the low expansion ceramic product are weighed according to a formula, and then the low expansion ceramic product is obtained through ball milling, screening, iron removal, filter pressing and dehydration, mud kneading, molding, glazing and firing.
[0067] The screening process is to pass through a 325-mesh sieve with a sieve residue of 0.05%.
[0068] The molding process adopts a grouting molding method.
[0069] The glazing process is to first glaze by dipping glaze method and then glaze by spraying glaze method.
[0070] The firing process has a maximum firing temperature of 1230° C., which is maintained at the maximum temperature for 45 minutes and then rapidly cooled to 1150° C., maintained at the maximum temperature for another 50 minutes and then naturally cooled, and the firing cycle is 10.5 hours.
[0071] The water absorption rate of the low expansion ceramic product is 0.39% and the expansion coefficient is 2.4 x 10 -6 / ℃, thermal shock resistance is 350℃~20℃, one-time water cooling will not crack.
[0072] The above expansion coefficient is tested by using a thermal expansion meter, model DIL402C thermal expansion tester.
[0073] The above water absorption is tested by using a water absorption meter, model TXY-320 water absorption meter.
[0074] The above thermal shock resistance is tested by a thermal stability tester, model SQ005 thermal stability tester.
[0075] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the principles and spirit of the present invention are included in the protection scope of the present invention.
Claims
1. A low expansion ceramic product made from glass-ceramic scraps, characterized in that: The low expansion ceramic product body raw material formula is composed of 40-50wt% of microcrystalline glass scraps, 35-42wt% of halloysite, 8-12wt% of talc, 5-10wt% of burned datong clay, 1-5wt% of tantalum oxide, and 1-5wt% of niobium oxide in weight percentage.
2. The low expansion ceramic product according to claim 1, characterized in that: The chemical composition of the microcrystalline glass scraps is: SiO2 52.9-59wt%, Al2O3 25.2-31.1wt%, CaO 0.4-0.6wt%, MgO 2.6-3.9wt%, K2O 0.2-0.8wt%, Na2O 1.4-1.9 wt%, B2O3 5.5-8.8 wt%, Li2O 4.22-5.68 wt%, and the ignition loss is 1.2-3.2 wt%.
3. The low expansion ceramic product according to claim 1, characterized in that: The microcrystalline glass scraps are waste materials after microcrystalline glass is edged, punched and cut.
4. The method for preparing the low expansion ceramic product according to claim 1, characterized in that: The green body raw materials of low expansion ceramic products are weighed according to the formula, and then subjected to the processes of ball milling, screening, iron removal, filter pressing and dehydration, mud kneading, molding, glazing and firing to obtain low expansion ceramic products.
5. The preparation method according to claim 4, characterized in that: The screening process is to pass through a 325-mesh sieve with a sieve residue of 0.05%.
6. The preparation method according to claim 4, characterized in that: The forming process adopts a rolling forming or a grouting forming method.
7. The preparation method according to claim 4, characterized in that: The glazing process is to first glaze by dipping glaze method and then glaze by spraying glaze method.
8. The preparation method according to claim 4, characterized in that: The sintering process has a maximum sintering temperature of 1220-1240° C., maintaining the maximum temperature for 45-60 minutes, rapidly cooling to 1150° C., maintaining the temperature for another 30-60 minutes, and then naturally cooling, and the sintering cycle is 10-12 hours.
9. The preparation method according to claim 4, characterized in that: The water absorption rate of the low expansion ceramic product is ≤0.5%, and the expansion coefficient is ≤2.5x10 -6 / ℃, thermal shock resistance is 350℃~20℃, one-time water cooling will not crack.
Citation Information
Patent Citations
Method for preparing dichroite heat proof / refractory materials
CN101381240A